2020
DOI: 10.21106/ijma.421
|View full text |Cite
|
Sign up to set email alerts
|

Reducing False Negative PCR Test for COVID-19

Abstract: As the SARS-CoV-2 (COVID-19) pandemic spreads rapidly, there is need for a diagnostic test with high accuracy to detect infected individuals especially those without symptoms. Real-time polymerase chain reaction (RT-PCR) is a common molecular test for diagnosing SARS-CoV-2. If some factors are not taken into consideration when performing this test, it can have a relatively large number of false negative results. In this article, we discuss important considerations that could lead to false negative test reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The possible reasons of PCR-test negativity could be false-negative results due to (i) inaccurate or low sensitivity test kits, (ii) incorrect nasopharyngeal swab technique, (iii) testing outside of the optimal time period (too early or too late) during low viral load and (iv) contamination of test samples [ 30 33 ]. Another potential reason might be a genetic diversity within species of SARS-CoV-2 [ 31 , 34 ]. In the reported studies, the PCR-test false negative rate ranged from 2 to 50% [ 35 , 36 ], however, in our data the PCR-test negative cases reached 94,5% among all PCR-tested cases.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons of PCR-test negativity could be false-negative results due to (i) inaccurate or low sensitivity test kits, (ii) incorrect nasopharyngeal swab technique, (iii) testing outside of the optimal time period (too early or too late) during low viral load and (iv) contamination of test samples [ 30 33 ]. Another potential reason might be a genetic diversity within species of SARS-CoV-2 [ 31 , 34 ]. In the reported studies, the PCR-test false negative rate ranged from 2 to 50% [ 35 , 36 ], however, in our data the PCR-test negative cases reached 94,5% among all PCR-tested cases.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR test for the COVID-19 diagnosis have several limitations, such as a considerable rate of false negative results [ 10 , 11 ], which are partially due to quality of sampling, the type of sample used, the viral load, and the time after infection at which sample is taken [ 34 ]. Despite this, it continues being the best technique to diagnose COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential reasons for negative nasopharyngeal PCR tests including reduced viral load, transient viral dissemination or collection and storage errors. Research has shown a median false negative rate of COVID-19 nasopharyngeal RT-PCR of 38% on the day of symptom onset and maximum COVID-19 replication in the throat seen 5 days after symptom onset 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%